Dysregulation of focal adhesion kinase upon Toxoplasma gondii infection facilitates parasite translocation across polarised primary brain endothelial cell monolayers. (27th June 2019) - Ross, Emily C.; Olivera, Gabriela C.; Barragan, Antonio
Abstract: The apicomplexan parasite Toxoplasma gondii invades tissues and traverses non‐permissive biological barriers in infected humans and other vertebrates. Following ingestion, the parasite penetrates the intestinal wall and disseminates to immune‐privileged sites such as the brain parenchyma, after crossing the blood–brain barrier. In the present study, we have established a protocol for high‐purification of primary mouse brain endothelial cells to generate stably polarised monolayers that allowed assessment of cellular barrier traversal by T. gondii . We report that T. gondii tachyzoites translocate across polarised monolayers of mouse brain endothelial cells and human intestinal Caco2 cells without significantly perturbing barrier impermeability and with minimal change in transcellular electrical resistance. In contrast, challenge with parasite lysate or LPS increased barrier permeability by destabilising intercellular tight junctions (TJs) and accentuated transmigration of T. gondii . Conversely, reduced phosphorylation of the TJ‐regulator focal adhesion kinase (FAK) was observed dose‐dependently upon challenge of monolayers with live T. gondii but not with parasite lysate or LPS. Pharmacological inhibition of FAK phosphorylation reversibly altered barrier integrity and facilitated T. gondii translocation. Finally, gene silencing of FAK by shRNA facilitated transmigration of T. gondii across epithelial and endothelial monolayers. Jointly, the data demonstrate that T. gondii infection transiently alters the TJ stability through FAK dysregulation to facilitate transmigration. This work identifies the implication of the TJ regulator FAK in the transmigration of T. gondii across polarised cellular monolayers and provides novel insights in how microbes overcome the restrictiveness of biological barriers.